A NOVEL STRATEGY FOR MULTILEVEL CASCADED INVERTERS (MLCI) UNDER UNBALANCED DC SOURCES - Manoj, A.; Kumar, K V Sai (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
This paper introduces a pulse width-modulation strategy to achieve balanced line-to-line output voltages and to maximize modulation index over the range of linear modulation where the output voltage can be linearly adjusted in the multilevel cascaded inverter (MLCI) functioning under unbalanced dc-link conditions. In these conditions, the linear modulation range is lowered, and a considerable output voltage imbalance may occur as voltage references increase. In order to study these effects, the voltage vector space for MLCI is examined in detail. From this analysis, the theory behind the output voltage imbalance is analyzed, and the maximum linear modulation range obtainable taking into consideration an unbalanced dc-link condition is evaluated. Thereafter, a strategy based on neutral voltage modulation is introduced to obtain the output voltage balance and as to extend the linear modulation range up to the maximum point in theory. In this method, very large dc-link imbalance distorts the balancing of the output voltages. This limitation is also discussed. The simulation for a seven-level phase-shifted modulated MLCI for electric vehicle traction drive illustrate that the proposed method proves to be efficient in balancing the line-to-line output voltages and also in maximizing the range of linear modulation involving the unbalanced dclink conditions.